Leaving Home: The Challenges of Black-African International Students Prior to Studying Overseas - Caldwell, Elizabeth Frances; Hyams-Ssekasi, Denis (Journal of International Students, 2016)
Much of the literature on international students centres on their experiences once they arrive in their host countries. This study explores the preparations of Black-African students for leaving their home countries to study abroad. Semi-structured interviews were carried out with 50 Black-African students studying at one British university. The students spoke of the complex and frustrating process of obtaining visas and applying to university abroad as well as the tensions they felt in leaving their communities. These pressures were extensive and impacted their subsequent ability to adjust to life in their host institution. A greater understanding of the backgrounds of international students will enable higher education professionals to develop more culturally inclusive universities.